The Tewa World : Space, Time, Being and Becoming in a Pueblo Society - Ortiz, Alfonso (University of Chicago Press, 2012)
"This is a book that springs from richness. . . valuable not only for anthropologists and sociologists. . . the interested but unskilled layman will find a treasure trove as well. One thing seems certain. If this book does not become THE authority for the scholar, it will certainly never be ignored. Ortiz has done himself and his people proud. They are both worthy of the acclamation."--The New Mexican.